Low complexity local dimming algorithm for high quality head up displays in automotive vehicles - Kim, J. H.; Pyun, Y. J.; Oh, J. H.; Song, K. H.; Kim, Y. N.; Cho, J. H.; Yoon, C. Y.; Han, Y. H.; Nam, H. (Journal of Information Display, 2024)
We present a high image quality head up display (HUD) based on the local dimming liquid crystal display (LCD). The proposed HUD provides high white luminance to improve day-time visibility and low black luminance to cope with the postcard effect during the night by the local dimming technique. To reduce the computational complexity, the pixel-based boosting values for the pixel compensation are computed by simple bi-linear interpolation, complex power functions are implemented by look-up tables, some multiplications are replaced with the sums of shifted values, and the numbers of look-up tables and multipliers are reduced by sequential process. The simulation results of the proposed local dimming algorithm for 640×1280 LCD panel and 10×22 LED backlight ensure higher peak signal-to-noise ratio than 40 dB and larger power reduction performance than 73% over 7 HUD images. In addition, the postcard effect improvement is verified over images on LCD panel as well as windshield. Maximum luminance and contrast ratio on the windshield of the prototype HUD system are measured as 16,088 cd/m $ ^2 $ 2 and $ 342× {10^6} $ 342 × 10 6 :1.